2022
DOI: 10.1007/s11240-021-02216-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration via meristematic nodule culture in Paeonia ostii ‘Feng Dan’

Abstract: Tree peony (Paeonia sect. Moutan) is an economically important multipurpose woody plant in terms of its medical, ornamental and oil values, but its breeding and industrial development are severely limited due to inefficient traditional propagation methods and existing in vitro regeneration systems. Meristematic nodules (MNs) are an attractive alternative to solve this problem. This study first presented a protocol for in vitro regeneration of P. ostii ‘Feng Dan’ via MN culture with four consecutive steps, incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
3
5
1
Order By: Relevance
“…Histological examination con rmed this morphogenic response. This is contrary to previous conclusion that callus formation was necessary for MNs induction in tree peony (Xu et al 2022a). In fact, there were two morphogenesis pathways has been reported on MNs induction, direct (Moyo et al 2009;Ferreira et al 2009;Piéron et al 1998) and indirect with callus formation (Fortes and Pais 2000; Batista et al 2000).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Histological examination con rmed this morphogenic response. This is contrary to previous conclusion that callus formation was necessary for MNs induction in tree peony (Xu et al 2022a). In fact, there were two morphogenesis pathways has been reported on MNs induction, direct (Moyo et al 2009;Ferreira et al 2009;Piéron et al 1998) and indirect with callus formation (Fortes and Pais 2000; Batista et al 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…According to Xu et al (2022a), CPPU and TDZ, two kinds of cytokinin with high activity, played remarkably positive roles in MNs induction and shoots regeneration from callus. Meanwhile, DO and direct MNs induction only occurred in DM containing TDZ or CPPU in this research, but not in presence of BA, which further supported previous speculation that high level of cytokinin was indispensable for differentiation (Xu et al 2022a;Meng et al 2017). The result that TDZ + NAA, CPPU + NAA treatment in DIM had a better effect on the induction of MNs and DO than BA + NAA treatment also consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No somatic embryogenesis was observed on any of the tested media combinations. Similar to a study on tree peony 15 , the regeneration of Xanthosoma involved four distinct phases that included callus with multiple meristematic regions, pre- nodules, meristematic nodules and shoot primordia. Formation of meristematic nodules either directly or indirectly via callogenesis has been reported in a number of species including Acacia mangium 16 , Eucalyptus globulus 17 , Humulus lupulus 18 , 19 , Populus euphratica 20 , Sclerocarya birrea 21 etc.…”
Section: Resultsmentioning
confidence: 95%
“…Similar results have been reported for S. hybrida [ 17 ] and S. plebeia [ 22 ]. Additionally, the ratio of cytokinin and auxin being applied can alter their interaction and impose a significant effect on shoot regeneration and proliferation [ 38 , 39 , 40 ]. We found that the combination of 3 mg L −1 cytokinin and 0.1 mg L −1 auxin was the most effective in promoting shoot proliferation.…”
Section: Discussionmentioning
confidence: 99%